Before the Memory Fades: Measuring Long Term Memory in Older Adults - Jeb Schenck (Adult Education Research Conference, 2000)
An instrument was designed to measure visual memory span, a common form of memory used by adult learners. The instrument tested 239 older adults, using color photographs of household objects, which were later recalled. A number of significant variables were found and the instrument is believed suitable for examining the efficacy of adult instructional methods.